2009
DOI: 10.1175/2008jas2857.1
|View full text |Cite
|
Sign up to set email alerts
|

Nonstationary Synchronization of Equatorial QBO with SAO in Observations and a Model

Abstract: It has often been suggested that the period of the quasi-biennial oscillation (QBO) has a tendency to synchronize with the semiannual oscillation (SAO). Apparently the synchronization is better the higher up the observation extends. Using 45 yr of the 40-yr European Centre for Medium-Range Weather Forecasts (ECMWF) Re-Analysis (ERA-40) data of the equatorial stratosphere up to the stratopause, the authors confirm that this synchronization is not just a tendency but a robust phenomenon in the upper stratosphere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 37 publications
2
25
0
Order By: Relevance
“…It has also been found that the QBO and the SAO interact with each other. For example, the QBO and SAO periods are often synchronized (e.g., Dunkerton and Delisi, 1997;Krismer et al, 2013), and it has been suggested that the eastward phase of the SAO can initiate an eastward phase of the QBO (e.g., Kuai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It has also been found that the QBO and the SAO interact with each other. For example, the QBO and SAO periods are often synchronized (e.g., Dunkerton and Delisi, 1997;Krismer et al, 2013), and it has been suggested that the eastward phase of the SAO can initiate an eastward phase of the QBO (e.g., Kuai et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…We follow Kuai et al (2009) in utilising data extracted from the ERA-40 global reanalyses obtained by the European Centre for Medium Range Weather Forecasts (ECMWF; Uppala et al, 2005), also supplemented by additional analyses since 2005 in the ERA-interim dataset (e.g. Dee and Uppala, 2009;Dee et al, 2011).…”
Section: Datasetsmentioning
confidence: 99%
“…Further indications that the period of the QBO might adopt a bimodal distribution linked to periods commensurate with the annual cycle were apparent in the model simulations of Scaife et al (2002), though this was less evident in their analyses of observations. Recent research by Kuai et al (2009) has provided further evidence of intermittent, but frequently coherent, phase alignment between the QBO and stratospheric SAO, in which it was concluded that the westerly phase of the QBO (hereafter the w-QBO) only starts typically when the westerly phase of the SAO (w-SAO) has descended to approximately 7 hPa. To corroborate this apparently active synchronization of the two oscillations, Kuai et al determined the period between successive reversals of the zonal wind within each QBO cycle contained within the ERA-40 reanalysis dataset (Uppala et al, 2005) and found that the QBO did not exhibit a continuous range of periods, but occurred more or less at random with a period of either 24 or 30 months, i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maraun and Kurths (2005) found evidence for phase synchronization between the El Niño-Southern Oscillation (ENSO) index and variations in the Indian Monsoon, while Feliks et al (2010) detected phase synchronization between various climate indicators in the middle East and the North Atlantic Oscillation (Hurrell et al, 2003) on timescales of 7-8 years. On annual/seasonal timescales, Gruzdev and Bezverkhny (2000), Kuai et al (2009), and Read and Castrejon-Pita (2012), showed that the stratospheric Quasi-Biennial Oscillation (QBO) was phasesynchronized with the annual cycle in that its period was found to be entrained to a rational ratio of the annual period, although this ratio evidently fluctuated chaotically on timescales of several years. Evidence of partial phase synchronization of the ENSO index to the annual cycle was also found by Stein et al (2011).…”
Section: Introductionmentioning
confidence: 99%